(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article presents opinions on the interrelationship of culture and spirituality, the importance of cultural reforms in creating a new spiritual environment. The main aspects of the reforms implemented in our country regarding the creation of a new spiritual space have been analyzed.